Combined metabolic activators therapy ameliorates liver fat in nonalcoholic fatty liver disease patients. Issue 10 (25th October 2021) - Zeybel, Mujdat; Altay, Ozlem; Arif, Muhammad; Li, Xiangyu; Yang, Hong; Fredolini, Claudia; Akyildiz, Murat; Saglam, Burcin; Gonenli, Mehmet Gokhan; Ural, Dilek; Kim, Woonghee; Schwenk, Jochen M; et al.
Abstract: Nonalcoholic fatty liver disease (NAFLD) refers to excess fat accumulation in the liver. In animal experiments and human kinetic study, we found that administration of combined metabolic activators (CMAs) promotes the oxidation of fat, attenuates the resulting oxidative stress, activates mitochondria, and eventually removes excess fat from the liver. Here, we tested the safety and efficacy of CMA in NAFLD patients in a placebo‐controlled 10‐week study. We found that CMA significantly decreased hepatic steatosis and levels of aspartate aminotransferase, alanine aminotransferase, uric acid, and creatinine, whereas found no differences on these variables in the placebo group after adjustment for weight loss. By integrating clinical data with plasma metabolomics and inflammatory proteomics as well as oral and gut metagenomic data, we revealed the underlying molecular mechanisms associated with the reduced hepatic fat and inflammation in NAFLD patients and identified the key players involved in the host–microbiome interactions. In conclusion, we showed that CMA can be used to develop a pharmacological treatment strategy in NAFLD patients. SYNOPSIS: A placebo‐controlled human study shows that oral administration of Combined Metabolic Activators (CMA) reduces liver fat in nonalcoholic fatty liver disease (NAFLD) patients. CMA, consisting of L‐serine, nicotinamide riboside, N‐acetyl‐L‐cysteine, and L‐carnitine tartrate, has a profound effect on hepatic steatosis after only 70 days of treatment in NAFLD patients. CMA supplementation improved clinical parameters in NAFLD patients, such as reductions in aspartate aminotransferase, alanine aminotransferase, uric acid, and creatinine. The underlying mechanisms associated with the beneficial effect of CMA were revealed by a comprehensive analysis of plasma metabolomics and inflammatory proteomics as well as oral and gut metagenomics. Abstract : A placebo‐controlled human study shows that oral administration of Combined Metabolic Activators (CMA) reduces liver fat in nonalcoholic fatty liver disease (NAFLD) patients.